2014
DOI: 10.2500/ajra.2014.28.4048
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Type 2 Receptor Expression on Peripheral Blood Regulatory Lymphocytes in Patients with Allergic Rhinitis Treated with Specific Immunotherapy

Abstract: Natural pollen exposure results in up-regulation of H2R in Treg cells. Immunotherapy might transiently decrease the number of Treg-H2R(+) cells in the blood, which may be associated with their migration to the peripheral tissues. This study was part of the clinical trial registered in www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…However, emerging evidence suggests that EoE is associated with IgG4, and not mediated by IgE[38]. Interestingly, patients with allergic rhinitis have increased H2R expressing regulatory T cells at the peak of pollen season [39]which points towards the possible role of food allergens in promoting HR expression during EoE. It is also not known if HR expression is regulated by Th2 cytokines such as IL5 and IL13 which are overexpressed during active inflammation in EoE.…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence suggests that EoE is associated with IgG4, and not mediated by IgE[38]. Interestingly, patients with allergic rhinitis have increased H2R expressing regulatory T cells at the peak of pollen season [39]which points towards the possible role of food allergens in promoting HR expression during EoE. It is also not known if HR expression is regulated by Th2 cytokines such as IL5 and IL13 which are overexpressed during active inflammation in EoE.…”
Section: Discussionmentioning
confidence: 99%
“…pathway', 'Inflammation mediated by chemokine and cytokine signaling pathway' and 'Histamine H2 receptor mediated signaling pathway' participate in allergic inflammation (4,(63)(64). 'Apoptosis signaling pathway' (65) and 'Toll receptor signaling pathway' (66) are also involved in the pathology of AR. The expression of endotherin 2 is increased in cigarette-exposed asthmatic mice (67).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…mRNA expression studies confirmed the expression of H 1 , H 2 , and H 4 receptors whereas H 3 receptor mRNA was absent in CD8 + , CD4 + , and Th17 T cells 130–132 . The expression of H 2 receptor in Tregs from healthy subjects and patients with allergic rhinitis (AR) was demonstrated by flow cytometry 133 . Numerous studies evaluate the important role of histamine receptors using functional assays 114,115,133–138 (Figure 1).…”
Section: Histamine Modulation Of the Anti‐tumor Immunitymentioning
confidence: 87%